Self-Concept, Prosocial School Behaviors, Well-Being, and Academic Skills in Elementary School Students: A Whole-Child Perspective - Carina Wikman; Mara Westling Allodi; Laura Anne Ferrer-Wreder (MDPI AG, 2022)
Whole-child development focuses on supporting not only academic but also social emotional skills. This cross-sectional study's aim was to examine the associations between the child-rated self-concept and well-being, teacher-rated prosocial school behaviors, and academic skills (as measured by child performance tasks) and to examine if there were group differences by gender for these constructs. The sample was 143 s grade students (M age = 8 years old). The results indicate that self-concept correlated highly with well-being and moderately with prosocial behaviors, while academic skills correlated moderately with prosocial behaviors. The results also show that the boys had lower average prosocial behavior (teacher-rated) and self-concept (child-rated) ratings relative to the girls. The findings indicate that prosocial behavior, well-being, and self-concept can be measured in psychometrically sound and practically meaningful ways in Swedish elementary schools. Because many of the socioemotional and behavioral constructs were correlated with academic skills, these constructs could be important targets for early academic support interventions inspired by a whole-child approach.